Language and control in children's literature - Knowles, Murray, 1948-; Malmkjær, Kirsten (London ; New York : Routledge, 1996)
In this important and timely study Murray Knowles and Kirstin Malmjkaer examine the work of some of our most popular children's writers, from this and the last century, in order to expose the persuasive power of literature.
Book Cover; Title; Contents; Preface; Acknowledgements; Children's literature in England; Literature as a carrier of ideology: children's literature and control; Traditional juvenile fiction; Today's young reader; The fairytale; Fantasy fiction; Last thoughts; References; Index.
Includes bibliographical references (pages 267-275) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Children's stories, English -- History and criticism -- Theory, etc; Social control in literature; Discourse analysis, Literary; Children -- Books and reading; English language -- Rhetoric; Speech acts (Linguistics); Persuasion (Rhetoric); Exposition (Rhetoric); Histoires pour enfants anglaises -- Histoire et critique -- Théorie, etc; Contrôle social dans la littérature.; Discours littéraire.; Enfants -- Livres et lecture; Anglais (Langue) -- Rhétorique.; Actes de parole; literary criticism; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Exposition (Rhetoric); Children -- Books and reading; Discourse analysis, Literary; English language -- Rhetoric; Persuasion (Rhetoric); Social control in literature; Speech acts (Linguistics); Children's literature; Electronic books; Criticism, interpretation, etc